2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474181
|View full text |Cite
|
Sign up to set email alerts
|

In-liquid MEMS assembly by optical trapping

Abstract: This paper presents a novel in-liquid method to manipulate and micro-assemble MEMS in 3D by means of holographic optical trapping and hydrophobic interaction. Up to eight traps can be simultaneously generated with a trapping stiffness of 5 pN/µm each. SU8 cylinders (10µm diameter, 10µm-40µm height) were used as test MEMS, which could be translated with a speed of 6µm/s and rotated at 30 rpm. All forces were calibrated by video tracking the Brownian motion of the trapped MEMS and applying Boltzmann statistics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[15][16][17][18] However, the integration of heterogeneous (dissimilar) nanoscale components, which is required for self-contained probes, remains a challenge. So far such integration has been demonstrated only for micrometer-scale components, 12,[19][20][21][22][23][24][25] and it has been shown that heterogeneous integration can be done in a very efficient way by parallel and unsupervised self-assembly. [26][27][28][29] Micro-and nanoscale components are typically fabricated on rather thick (down to 25 lm, typically 200-300 lm thick) and large (down to 25 lm, typically 5-15 mm lateral dimensions) dies due to practical limitations regarding die a) Present address: International Iberian Nanotechnology Laboratory, Av.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] However, the integration of heterogeneous (dissimilar) nanoscale components, which is required for self-contained probes, remains a challenge. So far such integration has been demonstrated only for micrometer-scale components, 12,[19][20][21][22][23][24][25] and it has been shown that heterogeneous integration can be done in a very efficient way by parallel and unsupervised self-assembly. [26][27][28][29] Micro-and nanoscale components are typically fabricated on rather thick (down to 25 lm, typically 200-300 lm thick) and large (down to 25 lm, typically 5-15 mm lateral dimensions) dies due to practical limitations regarding die a) Present address: International Iberian Nanotechnology Laboratory, Av.…”
Section: Introductionmentioning
confidence: 99%